The Sensitivity Profile of Santri Towards Energy Saving Behavior (Case Study at the Pondok Pesantren Putri Jagad 'Alimussirry) - Rofi'ah, Alfiatur; Handriyan, Aris (Journal Intellectual Sufism Research (JISR), 2020)
Abstract. Pondok Pesantren Putri Jagad 'Alimussirry is one of the Islamic boarding schools in the city of Surabaya. The majority of those living in this pesantren are students and students who are actively studying. Santri (Ø§Ù„Ø³Ù†ØªØ±ÙŠ) based on the review of their actions are "People who adhere to the Qur'an and follow the Sunnah of the Prophet SAW and are firm in their stance." This is the meaning by relying on history and reality that cannot be replaced and changed forever. Santri in general is a term for someone who has attended Islamic religious studies in a place called a pesantren, usually stays in that place until his education is completed. Electricity is a habit carried out by individuals (individuals) or community groups in utilizing sources of electrical energy according to their needs and using them wisely. Pondok Pesantren Putri Jagad 'Alimussirry on the behavior of saving electrical energy and knowing the important role of energy saving behavior for students of the Pondok Pesantren Putri Jagad 'Alimussirry. With this research it is expected that the balance of the santri in the use and utilization of electrical energy